2015
DOI: 10.1111/bcp.12650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lopinavir/ritonavir on the pharmacokinetics of selexipag an oral prostacyclin receptor agonist and its active metabolite in healthy subjects

Abstract: AIMSThis study investigated the effect of a fixed dose combination of lopinavir/ritonavir on the pharmacokinetics (PK) of selexipag and its active metabolite ACT-333679. METHODSThis was an open label, randomized, single centre, two way, crossover study. Twenty healthy male subjects were treated with a single dose of 400 μg selexipag alone and in combination with multiple doses of lopinavir/ritonavir (400/100 mg) twice daily. RESULTSThe results showed that lopinavir/ritonavir approximately doubled the exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
2
25
0
3
Order By: Relevance
“…Therefore, if rifampicin and selexipag are not taken simultaneously, the full effect of CYP2C8 induction on the PK of selexipag will most likely be larger than that observed in the present study. Taking into consideration the results of the DDI study with lopinavir/ritonavir , which showed a minor effect of OATP1B1 and OATP1B3 inhibition on the PK of ACT‐333679, the full inductive effect of rifampicin on the PK of ACT‐333679 (responsible for the majority of the drug effect) in such situations probably will not be markedly different from that observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if rifampicin and selexipag are not taken simultaneously, the full effect of CYP2C8 induction on the PK of selexipag will most likely be larger than that observed in the present study. Taking into consideration the results of the DDI study with lopinavir/ritonavir , which showed a minor effect of OATP1B1 and OATP1B3 inhibition on the PK of ACT‐333679, the full inductive effect of rifampicin on the PK of ACT‐333679 (responsible for the majority of the drug effect) in such situations probably will not be markedly different from that observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the DDI study with selexipag and lopinavir/ritonavir showed only a minor change in C max and no change in the AUC for ACT‐333679, indicating the low dependency of ACT‐333679 on CYP3A4 enzymes and OATP transporters. Therefore, the pronounced effect of gemfibrozil on AUC, C max and t ½ of ACT‐333679 is most likely due to the inhibition of CYP2C8 and indicates the importance of the CYP2C8 pathway in the disposition of ACT‐333679.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, both selexipag and ACT‐333679 have been found to be weak substrates of OATP1B1 and OATP1B3, whereas selexipag alone is a weak substrate of the efflux pump P‐gp. Because lopinavir and ritonavir are known inhibitors of OATP1B1, OATP1B3, CYP3A, and P‐gp, an open‐label, randomized, single‐center, 2‐way, crossover study was performed to evaluate the possible effect of the fixed‐dose combination of lopinavir/ritonavir on the PK of selexipag or its metabolite . This could also evaluate the tolerability of single‐dose selexipag when administered alone or in combination with lopinavir/ritonavir in this fixed combination.…”
Section: Epidemiology Of Pahmentioning
confidence: 99%
“…Food had no significant effect on exposure to selexipag and ACT-333679, but it decreased the rate of absorption, as shown by a decrease in C max and a delay in the median time to reach maximum plasma/blood concentration (t max ) of 1-1.5 h. The observed increase in exposure of 10 % for selexipag and decrease of 27 % for ACT-333679 is within the pharmacokinetic variability of the compound, which should also be viewed in the light of the low dose administered, in the microgram range [5,6,8]. Also relevant in this context is that in clinical practice, selexipag is used at an individualized dose of 200-1600 lg bid, reached after weekly up-titration [9].…”
mentioning
confidence: 90%
“…Regarding the formation of the metabolite, based on nonclinical findings, selexipag undergoes enzymatic hydrolysis by the hepatic carboxylesterase 1 to yield the active metabolite [8]. Thus the metabolite is mainly formed systemically, which is further supported by its delayed appearance in vivo.…”
mentioning
confidence: 99%